Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1099/mic.0.026054-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of partial rpoB gene sequence analysis for the identification of clinically important and emerging Acinetobacter species

Abstract: Bacteria belonging to the genus Acinetobacter are ubiquitous in soil and water. Only a few species, including Acinetobacter baumannii, and the unnamed Acinetobacter genomic species (gen. sp.) 3 and 13TU, which together with the soil organism Acinetobacter calcoaceticus are combined in the A. calcoaceticus-A. baumannii (Acb) complex, have been recognized as important nosocomial infectious agents. The ecology, epidemiology and pathology of most species are not yet well established. Lack of practical and accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(128 citation statements)
references
References 38 publications
(53 reference statements)
5
113
0
4
Order By: Relevance
“…Although all 11 bloodstream isolates were misidentified by the phenotypic identification methods using the Vitek 2, MicroScan, and API 20 NE systems, all were correctly identified as Acinetobacter GS 13BJ/14TU by rpoB gene (zone 2) sequencing, confirming the suitability of this region for species identification, as reported previously (13,27,28). Misidentification by commercial systems may have arisen due to limitations in existing databases and the lack of nonspecialized substrates for Acinetobacter GS 13BJ/14TU species identification, as reported previously (2,(29)(30)(31).…”
Section: Discussionsupporting
confidence: 52%
“…Although all 11 bloodstream isolates were misidentified by the phenotypic identification methods using the Vitek 2, MicroScan, and API 20 NE systems, all were correctly identified as Acinetobacter GS 13BJ/14TU by rpoB gene (zone 2) sequencing, confirming the suitability of this region for species identification, as reported previously (13,27,28). Misidentification by commercial systems may have arisen due to limitations in existing databases and the lack of nonspecialized substrates for Acinetobacter GS 13BJ/14TU species identification, as reported previously (2,(29)(30)(31).…”
Section: Discussionsupporting
confidence: 52%
“…Rodents are considered to be important reservoirs of bartonellae, as they host a great variety of Bartonella species and strains (Birtles et al, 2001;Kosoy et al, 2012). To date, 417 Bartonella species have been isolated from wild rodents (Gundi et al, 2004(Gundi et al, , 2009Kosoy, 2010;Sato et al, 2012). Moreover, several studies have reported a wider diversity of Bartonella genotypes that surpass the current classification of Bartonella species (Pretorius et al, 2004;Inoue et al, 2009;Gundi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, commercially available platforms and phenotypic identification methods used in clinical microbiology laboratories are unable to differentiate related species within the ACB complex, and, as such, infections are often reported clinically as "A. baumannii complex" or simply grouped together as "A. baumannii" (14). Molecular techniques, such as rpoB gene sequence analysis, are necessary to accurately identify ACB complex isolates to the species level (15,16).…”
mentioning
confidence: 99%